2018
DOI: 10.2196/10085
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Preferences Toward a Hypothetical Trial of an Internet-Administered Psychological Intervention for Parents of Children Treated for Cancer: Web-Based Survey

Abstract: BackgroundClinical trials are often challenged with issues of recruitment and retention. Little is known concerning general attitudes and preferences toward trial design and willingness to participate among parents of children treated for cancer. Furthermore, willingness to participate in internet-administered psychological interventions remains unexplored. In this study, we examined attitudes and preferences of the population regarding study procedures for a hypothetical trial of an internet-administered psyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The intervention is an internet-administered, guided, LICBT-based intervention (the EJDeR intervention (intErnetbaserad sJälvhjälp för förälDrar till barn som avslutat en behandling mot canceR)) 10. Following phase I of the Medical Research Council’s complex interventions framework,35 development of EJDeR was informed by a systematic review,36 qualitative interview studies,37 38 a single-arm trial,39 participatory action research40 and a cross-sectional online survey 41. A PRP group of two mothers and two fathers of a child treated for cancer informed further refinements 10.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The intervention is an internet-administered, guided, LICBT-based intervention (the EJDeR intervention (intErnetbaserad sJälvhjälp för förälDrar till barn som avslutat en behandling mot canceR)) 10. Following phase I of the Medical Research Council’s complex interventions framework,35 development of EJDeR was informed by a systematic review,36 qualitative interview studies,37 38 a single-arm trial,39 participatory action research40 and a cross-sectional online survey 41. A PRP group of two mothers and two fathers of a child treated for cancer informed further refinements 10.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Although research on mobile health among children with cancer and their caregivers has recently gained momentum, the development of applications to promote psychological well-being in parents of children with cancer is poorly understood [ 8 ]. One survey on the attitudes and preferences surrounding mobile health found that approximately a quarter of parents of children with cancer were not in favour of online psychological interventions, if offered [ 12 ]. The enablers and barriers to attending online psychological interventions in these parents are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed methods, including a systematic review [ 6 ], interview studies [ 5 , 49 ], a single-arm trial [ 50 ], participatory action research [ 51 ], and a cross-sectional web-based survey [ 52 ] informed the initial development of EJDeR ( Figure 1 ). Subsequently, public [ 53 ] and professional involvement was adopted to improve the quality, relevance, and acceptability of the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Content has been closely developed alongside PRPs and has been informed by research identifying the experiences, distress, needs, and preferences for support of parents of children treated for cancer [5,6,[49][50][51][52]. Examples of tailoring for the population include (1) the use of case vignettes of parents using the intervention, which were informed by our previous research to enhance realism and relevancy [5,51]; (2) professional illustrations depicting parents throughout the intervention; (3) the inclusion of psychoeducation in the context of the situation of being a parent of a child treated for cancer (eg, fear of cancer reoccurrence); (4) the choice between attending the initial assessment session via telephone or videoconference [51]; and (5) the inclusion of a midintervention booster session [51].…”
Section: Tidier Checklist Item 9: Tailoring the Interventionmentioning
confidence: 99%